A narrative inquiry into the experience of negotiating the dominant stories of physical education: living, telling, re-telling and re-living. Issue 1 (2nd January 2016) - Casey, Ashley; Schaefer, Lee
Abstract : This paper explores the tensions that surfaced as a teacher of physical education (PE) shifted his 'stories to live by' [Clandinin, D. J., & Connelly, F. M. (1999). Storying and restorying ourselves: Narrative and reflection. In A. Y. Chen & J. Van Maanen (Eds.), The reflective spin: Case studies of teachers in higher education transforming action (pp. 15–23). Singapore: World Scientific] around PE. The tensions became explicit when his shifting 'stories to live by' bumped against dominant narratives of PE that shaped his professional knowledge landscape. Our inquiry is framed by Dewey's pragmatic ontology [(1938). Experience and education . New York, NY: Collier Books] and Clandinin and Connelly's [(1995). Teachers' professional knowledge landscapes . New York, NY: Teachers College Press] narrative conception of experience as the living and telling, re-telling and re-living, of stories of experience. We also draw on Connelly and Clandinin's [(1999). Storied identities: Storied landscapes. New York, NY: Teachers College Press] narrative conception of identity as 'stories to live by' which is an embodied, fluid and context-dependent view of identity as situated at the interface between personal practical knowledge and professional knowledge landscapes. We begin with situating this work within the broader spectrum of narrative research. We then describe the relational processes of re-telling the stories through narrative inquiry and finally explore the re-living of these stories in order to show the tensions that surfaced as Ashley's 'stories to live by' shifted. We engage in the narrative inquiry process of re-telling using the three-dimensional narrative inquiry space (with dimensions of place, sociality, temporality), to show tensions and shifting identities. We conceptualize these tensions as moments of autobiographical revisions [Carr, D. (1986). Time narrative and history . Bloomington: Indiana University Press]. These revisions are seen as a part of a person's struggle for narrative coherence; a struggle to compose a life in the professional knowledge landscape that is meaningful to each individual. In these moments of autobiographical revision we show the reflexive relationship between living, telling, re-telling and re-living of stories. We end by considering what we have learned about our own stories to live by through this process and theoretically and practically suggest ways other teacher educators and physical educators might benefit from engaging in narrative inquiry work.